Public discourse and socially responsible market behavior - Björn Bartling; Vanessa Valero; Roberto A. Weber; Lan Yao (University of Zurich, Department of Economics, 2024)
We investigate the causal impact of public discourse on socially responsible market behavior. Across three laboratory experiments, having market participants engage in public discourse generally increases market social responsibility. These positive impacts are robust to variation in several characteristics of the discourse. We provide evidence that discourse strengthens beliefs that others support socially responsible exchange. However, relaxing requirements to engage in discourse sharply reduces its effectiveness. Our findings suggest that campaigns encouraging discussion of appropriate market behavior can have sizable impacts on addressing inefficiencies due to market failures, but that policies encouraging broad public engagement may be important.
Keywords: C92; D62; D83; M14; 330; Public discourse; market failure; externalities; social responsibility; experiment; communication